Surrealism and Quebec Literature : History of a Cultural Revolution - Bourassa, Andre, G. (Book collections on Project MUSE., 2014)
In manifestos, poems, articles, and theatre pieces Bourassa€examines the nature of Quebec surrealism and its international context.€